2005
DOI: 10.1038/nbt1096
|View full text |Cite
|
Sign up to set email alerts
|

Systematic interpretation of genetic interactions using protein networks

Abstract: Genetic interaction analysis, in which two mutations have a combined effect not exhibited by either mutation alone, is a powerful and widespread tool for establishing functional linkages between genes. In the yeast Saccharomyces cerevisiae, ongoing screens have generated >4,800 such genetic interaction data. We demonstrate that by combining these data with information on protein-protein, prote in-DNA or metabolic networks, it is possible to uncover physical mechanisms behind many of the observed genetic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
495
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(517 citation statements)
references
References 38 publications
22
495
0
Order By: Relevance
“…Previous work has shown that it is possible to predict genetic interactions using physical protein-protein interaction networks Wong et al 2004;Kelley and Ideker 2005;Le Meur and Gentleman 2008). We therefore asked whether using functional interactionswhich extend beyond physical interactions-improves the predictive power of a network.…”
Section: Functional Network Are More Predictive Than Current Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that it is possible to predict genetic interactions using physical protein-protein interaction networks Wong et al 2004;Kelley and Ideker 2005;Le Meur and Gentleman 2008). We therefore asked whether using functional interactionswhich extend beyond physical interactions-improves the predictive power of a network.…”
Section: Functional Network Are More Predictive Than Current Proteinmentioning
confidence: 99%
“…These screens have highlighted the enormous extent to which mutations in one gene alter the phenotypic outcome of mutations in a second locus. Furthermore, the data from these screens show that most genetic interactions do not represent simple cases of ''redundancy'' between genes encoding similar biochemical functions Wong et al 2004;Kelley and Ideker 2005;Ulitsky and Shamir 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We find 228 of the 404 BPMs reported by Kelley and Ideker (2005) satisfy these criteria, as do 39 BPMs from Ulitsky and Shamir (2007b), 78 from Ma et al (2008), and 1062 from Brady et al (2009).…”
Section: Datamentioning
confidence: 90%
“…In order to systematically collect information on these functional relationships, high-throughput technologies in Saccharomyces cerevisiae have been developed to qualitatively identify synthetic sick/lethal (SSL) (aggravating) genetic interactions between gene pairs on a genomewide scale (3)(4)(5). While these methods have proven very powerful, it has become clear that individual SSL relationships between non-essential genes are often hard to interpret since they usually identify genes that function in different, potentially parallel pathways (6)(7)(8). Quantitative information on the entire spectrum of genetic interactions would provide a more comprehensive view of the cellular effects of gene mutation.…”
Section: Introductionmentioning
confidence: 99%